Projeto de Implantação de um sistema de informação geográfica - SIG para o Geopark Araripe - Beserra, Theóphilo Michel Àlvares Cabral (2011)
The Geoparks around the world are geological and paleontological sites that represent a significant part of the natural heritage biodiversity history culture archeology and other elements of a region having the same active role in sustainable development and economic development of their territory. Policies for the preservation of historic and cultural heritage are located within a radius of action of Geopark Araripe associated with this promotion are being worked on historical cultural activities in the areas of education in communication and social development. The present research proposes the direction of Geopark Araripe implementing a geographic information system - GIS aimed at streamlining and improving the methods of analysis representation and presentation of diagnostic information and searched the area using as a reference for the development of this project geographical studies and their application through geo. The geo-technologies are essential not only in the execution of mapping and monitoring of geographical space but also in organizing and structuring information in a single geographical properly georeferenced digital database facilitating the execution of analysis manipulation and query of spatial data. They have been constituted a fundamental allowance for diffusion of geographical knowledge decision-making strategy and actions in various areas. The proposed deployment of GIS will provide the project Geopark an improvement in technical and scientific knowledge a process of interdisciplinary work that has been applied in various fields of science providing researchers and scholars to discover information. The geography is included in the group of sciences that has been providing various segments of society the ability to streamline and enhance the information found and dispersed geographic area, geographic analysis tools over the years has evolved considerably this development is associated with technological and scientific development that man has been providing. The need to build display and disseminate instruments that can provide a full development potential of a city region or state is a tool that will provide a social and economic development more effectively. The participation of various segments of society in the elaboration of a major project such as the International Geopark presupposes the importance of environmental conservation oriented development and Geographic Information System contributes significantly in the development of a region the scene of numerous projects research and scientific works